Sleep in 21-Day Dry Immersion. Are Cardiovascular Adjustments Rapid Eye Movement Sleep-Dependent? - Bersenev, Evgeny Yu.; Ukraintseva, Yulia V.; Kovrov, Gennadiy V.; Yakhya, Yusef D.; Vassilieva, Galina Yu.; Tomilovskaya, Elena S.; Rukavishnikov, Ilya V.; Posokhov, Sergey I.; Orlov, Artemiy V.; Osetsky, Nikolay Yu.; Orlov, Oleg I. (Frontiers in Physiology, 2021)
Introduction: A decrease in sleep quality and duration during space missions has repeatedly been reported. However, the exact causes that underlie this effect remain unclear. In space, sleep might be impacted by weightlessness and its influence on cardiovascular function. In this study, we aimed at exploring the changes of night sleep architecture during prolonged, 21-day Dry Immersion (DI) as one of the ground-based models for microgravity studies and comparing them with adaptive changes in the cardiovascular system. Methods: Ten healthy young men were exposed to DI for 21 days. The day before (baseline, B-1), on the 3rd (DI3), 10th (DI10), and 19th (DI19) day of DI, as well as in the recovery period, one day after the end of DI (R+1), they were subjected to overnight polysomnography (PSG) and ambulatory blood pressure monitoring. Results: On DI3, when the most severe back pain occurred due to the effects of DI on the spine and back muscles, the PSG data showed dramatically disorganized sleep architecture. Sleep latency, the number of awakenings, and the duration of wake after sleep onset (WASO) were significantly increased compared with the B-1. Furthermore, the sleep efficiency, duration of rapid eye movement sleep (REM), and duration of non-rapid eye movement stage 2 decreased. On DI10, subjective pain ratings declined to 0, and sleep architecture returned to the baseline values. On DI19, the REM duration increased and continued to rise on R+1. An increase in REM was accompanied by rising in the nighttime heart rate (HR), which also shows the most significant changes after the end of DI. On DI19 and R+1, the REM duration showed opposite correlations with the BP parameters: on DI19 it was negatively associated with the systolic BP (SBP), and on R+1 it was positively correlated with the diastolic BP (DBP). Conclusion: An increase in REM at the end of DI and in recovery might be associated with regulatory changes in the cardiovascular system, in particular, with the reorganization of the peripheral and central blood flow in response to environmental changes.